BEHAVIORS OF THERMOELASTIC PROPERTIES IN NI-TI BASED SHAPE MEMORY ALLOYS, PROCESSED BY METAL FORMING TECHNIQUES - Tenório Luna da Silva, Tarsila; Virgolino, Filipe; Silva, Niedson; Oliveira, Carlos; Araújo, Carlos; De Araujo Filho, Oscar Olimpio; Gonzalez, Cezar (IIUM Engineering Journal, 2023)
In this work, the thermoelastic properties of Ni-Ti shape memory alloys (SMA) processed by conventional rolling and equal channel angular extrusion (ECAE) were investigated. SMAs have two phases: Austenite (at high temperature) and Martensite (at low temperature). The samples were compared under five different thermal and processing conditions: homogenized, rolled, rolled-annealed, extruded, and extruded-annealed. The homogenized sample served as a reference. The samples were analyzed by differential scanning calorimetry (DSC) to determine the thermoelastic transformation temperatures. Images were taken using scanning electronic microscopy (SEM) in conjunction with energy dispersive spectroscopy (EDS). The dynamic area was completed for two tests: under constant load bending (simulation of the memory effect to determine the reversible thermoelastic strain) and dynamic mechanical analysis (DMA). The results showed that the plastic forming processes alter the properties, especially for samples exposed to the ECAE, which can block the martensitic phase. However, R-phase (a rhombohedral phase), that can appear at low temperatures before the martensitic phase, emerges totally when the extruded sample suffers annealing. The images of SEM, confirmed by EDS, show that any type of forming process and the presence of precipitates have a significant influence on the behavior of the elastic property. It was found that extrusion has a greater effect on the restoring properties of the alloys than rolling. This analysis is of great importance for the use of SMA in applications requiring high mechanical strength combined with the functional properties of shape recovery through martensitic phase transformations. ABSTRAK: Kajian ini adalah berkaitan sifat-sifat bentuk aloi ingatan (SMA) termoelastik Ni-Ti yang diproses melalui penggelek konvensional dan penyemperitan sudut saluran sama (ECAE). SMA mempunyai dua peringkat: Austenit (pada suhu tinggi) dan Martensit (pada suhu rendah). Sampel dibandingkan pada lima tahap kepanasan dan proses iaitu: percampuran, penggulungan, penggulungan-rataan, perataan dan penyemperitan-rataan. Sampel campuran yang dihomogenkan dijadikan sebagai sampel rujukan. Sampel dianalisis dengan pengimbas kalorimetri pembezaan (DSC) bagi menentukan suhu transformasi termoelastik. Imej diambil menggunakan pengimbas mikroskop elektronik (SEM) bersama spektroskopi penyebaran tenaga (EDS). Kawasan dinamik diuji dengan dua ujian: di bawah lenturan beban malar (simulasi kesan memori bagi menentukan terikan termoelastik boleh balik) dan analisis mekanik dinamik (DMA). Dapatan kajian menunjukkan bahawa proses pembentukan plastik telah mengubah sifat, terutama pada sampel yang terdedah kepada penyemperitan sudut saluran sama ECAE, yang boleh menyekat fasa martensit. Walau bagaimanapun, fasa-R (fasa rombohedral) yang boleh muncul pada suhu rendah sebelum fasa martensitik, muncul sepenuhnya apabila sampel tersemperit mengalami penyepuhlindapan (penyemperitan-rataan). Imej pengimbasan mikroskop elektron, seperti yang dibuktikan dengan spektroskopi penyebaran tenaga (EDS), menunjukkan bahawa apa-apa jenis proses pembentukan dan kehadiran mendakan mempunyai pengaruh kuat terhadap sifat elastik. Dapatan kajian juga mendapati bahawa penyemperitan mempunyai kesan yang lebih besar terhadap sifat pemulihan aloi berbanding proses penggulungan. Analisis ini sangat penting bagi penggunaan bentuk aloi ingatan (SMA) dalam aplikasi yang memerlukan kekuatan mekanikal yang tinggi bersama sifat pemulihan bentuk melalui transformasi fasa martensit.